Forward Reverse Starter Motor Control With Internet Of Things (IoT) - ISHAK, MUHAMMAD AIMAN; LAM, HONG YIN (Progress in Engineering Application and Technology, 2023)
The project aims to develop a motor control system integrated with IoT technology. The system utilizes an ESP8266 microcontroller as the main control unit, a current sensor for input monitoring, a relay for motor control, and an LCD display to visualize the motor’s condition. The relay is connected to the contactor, allowing for seamless control of motor operation. The Blynk application serves as the user interface, enabling remote motor control and real-time monitoring of the current value. The primary objective of the project is to provide convenient motor control and enhance safety through automatic motor shutdown in case of excessive current flow. The Blynk application empowers users to remotely switch the motor on or off based on their requirements. Additionally, users can monitor the real-time current value through the application, allowing for proactive identification of potential issues. The system employs the current sensor to continuously measure the motor’s current consumption. If the current exceeds 6A, indicating a potential overload or fault condition, the system automatically shuts off the motor for protection purposes. This feature enhances the motor’s operational safety and minimizes the risk of damage or accidents. The project combines the power of IoT technology, microcontroller-based control, and sensor integration to create a versatile motor control system. The integration of the Blynk application enables remote control and monitoring, making the system user-friendly and accessible from anywhere. The project contributes to improved motor control efficiency, convenience, and safety in various applications, such as industrial and residential settings.